Investigating the influence of urban green spaces on urban heat island mitigation – taking four districts in Shijiazhuang as an example - Nan Zhang; Qiuning Ding; Haitao Wang (Journal of Environmental Engineering and Landscape Management)
The primary objective of this scholarly investigation is to elucidate the intricate interplay between the urban heat island (UHI) effect and municipal green spaces. The geographical focus includes the four areas with the highest urbanization rate in Shijiazhuang, China. To conduct this survey, ECOSTRESS remote sensing imagery was acquired during distinct temporal intervals–morning, midday, and evening. The data were collected using the equal-scale city blocks performed by the OpenStreetMap urban network and ECOSTRESS remote sensing images at different times (morning, noon and evening). Surface temperature inversion of satellite images was performed using ArcGIS 10.7 software to obtain surface temperature. The overarching aim was to discern the nuanced impact of urban parks on the surface temperatures of their proximate environs during the summer season. The findings of this investigation revealed that, in order to effectively ameliorate the discernible heat island effect (SUH), rejuvenation initiatives ought to be directed toward sites maintaining a distance from green spaces within the range of 160 to 370 meters. Furthermore, augmentation of green space configurations is recommended in vicinities characterized by building densities falling within the range of 0.2 to 0.3. Notably, in locales marked by high building density, park layouts should adhere to a more regularized design during the renovation process. Additionally, it is advisable to ensure that the spatial separation between distinct urban parks exceeds 900 meters. These empirical insights are poised to enhance the comprehension of urban planners regarding the intricate dynamics through which urban parks exert influence on municipal surface temperatures. Furthermore, the discerned patterns furnish pragmatic guidance for mitigating the heat island effect, thereby offering invaluable recommendations for urban planning endeavors.